The Relationship between Hours of Domestic Services and Female Earnings: Panel Register Data Evidence from a Reform - Karin Halldén; Anders Stenberg (Institute for the Study of Labor (IZA), 2014)
In 2007, a tax discount reform in Sweden reduced prices of outsourced domestic services (ODS) by 50 percent. Unlike most previous studies, population register data enable us to directly link a proxy for relaxed time constraints, annual changes in households' tax discounts, to changes in earnings. We find that 60 percent of married women's freed hours are applied to labor market work, which tapers off when ODS corresponds to approximately three weeks of full time work. This is substantially higher than previously reported estimates. A causal interpretation is supported by "placebo tests", and we carefully outline the assumptions required.
Keywords: H2; J13; J22; 330; household work; outsourcing; female labor supply